DNA Profiling and the Challenges of Crime Management in Nigeria: The Case of The Nigeria Police Force - Nathaniel Nte, Ucheawaji; Nte, Ngboawaji Daniel; Enokie, Bribena Kelvin; Bienose, Onyeka (Universitas Negeri Semarang, 2019)
This research investigated DNA profiling and crime management in Nigeria. The major objective of the study was to find out whether the Nigeria Police are aware of how to use DNA optimally as a source of evidence in the investigation process. In Nigeria, the Nigeria Police is one of the leading agencies statutorily charged with the responsibility of providing internal security through fighting of crime. The police does this job by undertaking criminal investigation with a view to collecting evidence to be used for courtroom prosecution of criminal suspects. Since 1930 the Nigeria Police was established, it has relied mainly on the traditional (old school) method of criminal investigations based on eye witness testimonies and statements, the investigators sense of judgement and experience. Overwhelming evidence from this research points to the fact that the said method has proven ineffective, as may unsolved crimes, wrongful prosecution or conviction of innocent criminal suspects and failed courtroom prosecution litter the performance profiles of the Nigeria Police. The study concluded that the capacity level of the Nigeria Police to collect and preserve the DNA evidence as part of the agency's criminal investigation process and use same for courtroom prosecution has significant effect on the effort it makes to fight crime through DNA profiling, and that the availability or non availability of sophisticated DNA technology in Nigeria has significant effect on the effort the Nigeria police makes to fight crime through DNA profiling. The availability or non availability of a central DNA database in Nigeria has significant effect on the efforts of the Nigeria police makes to fight crime through DNA profiling.